Tips and tricks of ureteroscopy: consensus statement Part I. Basic ureteroscopy - Rukin, Nicholas J. (Cent European J Urol, 2015)
Ureteroscopy is fast becoming the first line treatment option for the majority of urinary tract stones. Ureteroscopy training can be performed in a variety of ways including simulation, hands on ureteroscopy courses and supervised operative experience. We report an “expert consensus view” from experienced endourological surgeons, on all aspects of basic ureteroscopic techniques, with a particular focus on avoiding and getting out of trouble while performing ureteroscopy. In this paper we provide a summary of treatment planning, positioning, cannulation of ureteric orifice, guidewire placement, rigid ureteroscopy and stone fragmentation.